2016
DOI: 10.1177/1029864915626968
|View full text |Cite
|
Sign up to set email alerts
|

Contextualising the relationship between music, emotions and the well-being of young people: A critical interpretive synthesis

Abstract: A convergent parallel design was used to interrogate two sets of literature produced by researchers investigating music, emotions and well-being: the first being 16 quantitative music psychology studies, the second being seven qualitative music therapy studies. A series of critical analyses examined some of the main assumptions that had influenced the design of the studies, largely related to the nomothetic or idiographic approaches adopted by the researchers, as well as beliefs about how music is best used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 69 publications
(105 reference statements)
1
32
0
1
Order By: Relevance
“…Other research shows that individual factors such as reward sensitivity, emotional sensitivity to music and absorption in music contribute to its effect on listeners ( Sandstrom and Russo, 2011 ; Loxton et al, 2016 ). Several recent studies have found that a tendency to ruminate or brood influences whether people listen to music in ways that are helpful or unhelpful to their mood ( McFerran and Saarikallio, 2013 ; Garrido and Schubert, 2015 ; McFerran, 2016 ). Music with lyrics may have a particularly powerful influence on the mood of adolescents who score more highly in ruminative thoughts than adults of older age groups ( Sütterlin et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other research shows that individual factors such as reward sensitivity, emotional sensitivity to music and absorption in music contribute to its effect on listeners ( Sandstrom and Russo, 2011 ; Loxton et al, 2016 ). Several recent studies have found that a tendency to ruminate or brood influences whether people listen to music in ways that are helpful or unhelpful to their mood ( McFerran and Saarikallio, 2013 ; Garrido and Schubert, 2015 ; McFerran, 2016 ). Music with lyrics may have a particularly powerful influence on the mood of adolescents who score more highly in ruminative thoughts than adults of older age groups ( Sütterlin et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, previous research has demonstrated that listening to music that is perceived as sad can intensify depression in listeners with ruminative tendencies (Garrido and Schubert, 2015a,b), and that people with depressive tendencies may struggle to regulate their emotional responses in musical contexts (McFerran, 2016). Since group settings and social feedback can intensify the emotions experienced in response to music, the possibility exists that group interactions around sad music could have an even more dangerous outcome for people with tendencies to depression.…”
Section: Introductionmentioning
confidence: 99%
“…The development of adaptive and flexible regulation tools during adolescence is crucial for youth's wellbeing and mental health. Depending on the used strategies, music can be a risk or protective factor (Miranda 2013;McFerran 2016). The affective outcomes and wellbeing implications are not explored in this chapter; however, it is worth noting that, according to this model, affective musical regulation impacts-positively or negatively-the adolescent's wellbeing through the cumulative process of affective outcomes.…”
Section: Affective Outcomes and Wellbeingmentioning
confidence: 99%